Estudios sobre la aplicación de ultrasonido en el procesamiento de alimentos - Pisco Mendo, Edgar Oswaldo (2013)
The objective of this research is to find studies related to the application of ultrasound in food processing. This begins with an overview of the new technologies in the food processing, information relating to ultrasound, the ultrasound sources, the parameters of the ultrasound and cavitation phenomenon as it has been established that this phenomenon is produced conservative effect of ultrasound. Studies also concerned about the microbiological effect of ultrasound, where we see how it is produced and what kind of cells are the most resistant to apply this technology to enter our field of study, the research conducted on the use of ultrasound in processes of great importance in food industry, where they have performed well as preserve the nutritional and organoleptic properties of the processed product. Finally I conclude with research regarding the use of ultrasound in a particular industry, the dairy industry, where applications such as homogenization is the most redeemable within this.